Paired evaluation of calvarial reconstruction with prototyped titanium implants with and without ceramic coating - Calderoni,Davi Reis (2014)
PURPOSE:To investigate the osseointegration properties of prototyped implants with tridimensionally interconnected pores made of the Ti6Al4V alloy and the influence of a thin calcium phosphate coating.METHODS: Bilateral critical size calvarial defects were created in thirty Wistar rats and filled with coated and uncoated implants in a randomized fashion. The animals were kept for 15, 45 and 90 days. Implant mechanical integration was evaluated with a push-out test. Bone-implant interface was analyzed using scanning electron microscopy.RESULTS: The maximum force to produce initial displacement of the implants increased during the study period, reaching values around 100N for both types of implants. Intimate contact between bone and implant was present, with progressive bone growth into the pores. No significant differences were seen between coated and uncoated implants.CONCLUSION:Adequate osseointegration can be achieved in calvarial reconstructions using prototyped Ti6Al4V Implants with the described characteristics of surface and porosity.